Effects of Parameter Uncertainties on Interaction between Submarine Telecommunication Cables and Lateral Seabed Movements. (20th August 2020) - Fu, Cuiwei; Qin, Xiaogang; Wang, Yu
Abstract : Submarine telecommunication cables are the physical backbone of the Internet. They are often buried shallowly beneath seabed and affected by seabed movements. Due to the long distance of cables and the complexity of submarine environment, interaction between cables and seabed movements inevitably involves various parameter uncertainties. However, effects of parameter uncertainties on submarine cable responses to seabed movements have not been fully investigated. This paper aims to address this problem using random finite element method (RFEM) that integrates finite element (FE) analysis with Monte Carlo simulation (MCS). First, deterministic FE analysis is performed to investigate cable responses to lateral seabed movements. Then MCS is implemented to study the effects of parameter uncertainties on cable responses. Statistical analysis of the MCS results is performed to prioritize the effects of parameter uncertainties on cable damage probability. Random field is also used to model spatial variability of soil parameters. Effect of the correlation length on cable damage probability is investigated. The results show that uncertainty of the anchored cable length L a has the most significant effect on cable damage probability, while the effects of uncertainties in soil friction angle ϕ and effective unit weight γ ′ are minor. Ignoring spatial variability of soil parameters may lead to significant misjudgment of cable damage risk.